A Cross-Sectional Analytical Study of Platelet Indices in Type 2 Diabetes Mellitus - Sharma, Bhavin Somabhai; Warpe, Bhushan M; Joshi, Shweta S (Annals of Pathology and Laboratory Medicine, 2025)
Background: Diabetes mellitus (DM) is a growing public health burden in India, projected to become the 'diabetic capital' of the world by 2030. Platelet activation plays a key role in the pro-thrombotic state associated with DM. Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), and Platelet Large Cell Ratio (P-LCR) are potential biomarkers to evaluate platelet activity and predict diabetic complications. Methods: A cross-sectional, single-visit analytical study were conducted at a tertiary care center in Bhuj, Gujarat, India between 1st June 2023 to 30th November 2024. Results: A total number of 130 cases each of non-diabetic and diabetic cases with or without complications were studied. The mean of MPV, PDW and P-LCR were statistically significantly increased in diabetic patients with complications than diabetic patients without complications and non-diabetic volunteer group. Poor glycemic control and raised FBS and PPBS blood sugar level cause increased risk of diabetic complications. However, no statistically significant differences were observed in RBS among all the study groups. Diabetic patients were divided into two groups according to their HbAlc levels: 3.1% in group A1 (mean HbAlc <6.5%) and 96.9% in group A2 (mean HbAlc ≥6.5%). However, platelet indices and blood sugar parameters in diabetes were not statistically significant between groups A1&A2. Conclusion: Our study suggests that increased platelet volume indices may contribute to the prothrombotic state in diabetes mellitus. The raised MPV, PDW and P-LCR can be considered as key biomarkers for early detection of impending diabetic complications.